Ex vivo electric power generation in human blood using an enzymatic fuel cell in a vein replica. Issue 74 (25th July 2016) - Pankratov, Dmitry; Ohlsson, Lars; Gudmundsson, Petri; Halak, Sanela; Ljunggren, Lennart; Blum, Zoltan; Shleev, Sergey
Abstract : Proof-of-principle demonstration of sustained electricity generation by a biofuel cell operating in an authentic human blood stream. Abstract : Here we report an enzymatic fuel cell in a vein replica that generates sustained electricity, enough to power an e-ink display, in an authentic human blood stream. We also detail a simple and safe approach for fuel cell evaluation under homeostatic conditions. Our results demonstrate proof-of-principle operation of a biocompatible and safe biodevice that could be implanted in superficial human veins, which we anticipate to be a starting point for more sophisticated investigations of personal sources of electricity.